Teacher Empowerment Strategies for Conflict Transformation and Peace Building in Kenya (Teacher Education through Flexible Learning in Africa (TETFLE), 2021)
The effects of violent conflict on education are enormous, and provision of quality education cannot be realised if teachers are not adequately trained to teach in conflict-prone areas. This reality prompted the study to investigate strategies to empower teachers in conflict transformation and peacebuilding. Guided by the Conflict Transformation Theory which proposes to identify the root causes of a conflict, and the use of creativity to transform the causes based on relationships and sub-systems that surround the conflict over time, a cross-sectional mixed methods study was conducted in Mt. Elgon region, Kenya. The study found that: for teachers to participate in conflict transformation there was a need for training in peace education and implementation of Life Skills Curriculum through various methods including distance education. Since then the government has developed education sector policy on peace education which provides for policy and curriculum initiatives, collaboration and partnerships to address challenges in peacebuilding and violent extremism. Initiatives to train teachers and education officers in peace education and implementation of the Life Skills Curriculum have been instituted. However, despite the efforts, peace education is not effectively taught in many schools due to inadequate teacher training. Equally, life skills education, one of the main subjects to promote peace education, is not effectively implemented. To mitigate this, the government has made several efforts to identify best practices to promote peace education and implement life skills, among them, teacher training on how to enhance peace education through mainstreaming and implementation of Life Skills Curriculum. There is need for further investigation on the current gaps in peace education in the wake of the curriculum review to Competency Based Curriculum in Kenya.
Keywords: Conflict; Conflict transformation; Life skills; Peace building; Violence